MVA-based vaccine candidates expressing SARS-CoV-2 prefusion-stabilized spike proteins of the Wuhan, Beta or Omicron BA.1 variants protect transgenic K18-hACE2 mice against Omicron infection and elicit robust and broad specific humoral and cellular immune responses - Pérez, Patricia; Astorgano, David; Albericio, Guillermo; Flores, Sara; Sánchez-Corzo, Cristina; Noriega, María A.; Sánchez-Cordón, Pedro J.; Labiod, Nuria; Delgado, Rafael; Casasnovas, José M.; Esteban, Mariano; García-Arriaza, Juan (Frontiers in Immunology, 2024)
Despite the decrease in mortality and morbidity due to SARS-CoV-2 infection, the incidence of infections due to Omicron subvariants of SARS-CoV-2 remains high. The mutations acquired by these subvariants, mainly concentrated in the receptor-binding domain (RBD), have caused a shift in infectivity and transmissibility, leading to a loss of effectiveness of the first authorized COVID-19 vaccines, among other reasons, by neutralizing antibody evasion. Hence, the generation of new vaccine candidates adapted to Omicron subvariants is of special interest in an effort to overcome this immune evasion. Here, an optimized COVID-19 vaccine candidate, termed MVA-S(3P_BA.1), was developed using a modified vaccinia virus Ankara (MVA) vector expressing a full-length prefusion-stabilized SARS-CoV-2 spike (S) protein from the Omicron BA.1 variant. The immunogenicity and efficacy induced by MVA-S(3P_BA.1) were evaluated in mice in a head-to-head comparison with the previously generated vaccine candidates MVA-S(3P) and MVA-S(3Pbeta), which express prefusion-stabilized S proteins from Wuhan strain and Beta variant, respectively, and with a bivalent vaccine candidate composed of a combination of MVA-S(3P) and MVA-S(3P_BA.1). The results showed that all four vaccine candidates elicited, after a single intramuscular dose, protection of transgenic K18-hACE2 mice challenged with SARS-CoV-2 Omicron BA.1, reducing viral loads, histopathological lesions, and levels of proinflammatory cytokines in the lungs. They also elicited anti-S IgG and neutralizing antibodies against various Omicron subvariants, with MVA-S(3P_BA.1) and the bivalent vaccine candidate inducing higher titers. Additionally, an intranasal immunization in C57BL/6 mice with all four vaccine candidates induced systemic and mucosal S-specific CD4+ and CD8+ T-cell and humoral immune responses, and the bivalent vaccine candidate induced broader immune responses, eliciting antibodies against the ancestral Wuhan strain and different Omicron subvariants. These results highlight the use of MVA as a potent and adaptable vaccine vector against new emerging SARS-CoV-2 variants, as well as the promising feature of combining multivalent MVA vaccine candidates.